Determination of the five parameter grain boundary character distribution of nanocrystalline alpha-zirconium thin films using transmission electron microscopy. (15th May 2017) - Ghamarian, I.; Samimi, P.; Rohrer, G.S.; Collins, P.C.
Abstract: Grain boundary engineering and other fundamental materials science problems (e.g., phase transformations and physical properties) require an improvement in the understanding of the type and population of grain boundaries in a given system – yet, databases are limited in number and spare in detail, including for hcp crystals such as zirconium. One way to rapidly obtain databases to analyze is to use small-grained materials and high spatial resolution orientation microscopy techniques, such as ASTAR™/precession electron diffraction. To demonstrate this, a study of grain boundary character distributions was conducted for α-zirconium deposited at room temperature on fused silica substrates using physical vapor deposition. The orientation maps of the nanocrystalline thin films were acquired by the ASTAR™/precession electron diffraction technique, a new transmission electron microscope based orientation microscopy method. The reconstructed grain boundaries were classified as pure tilt, pure twist, 180°-twist and 180°-tilt grain boundaries based on the distribution of grain boundary planes with respect to the angle/axis of misorientation associated with grain boundaries. The results of the current study were compared to the results of a similar study on α-titanium and the molecular dynamics results of grain boundary energy for α-titanium. Graphical abstract: Image